The outcome of vitrectomy with internal limiting membrane peeling for chronic macular hole at Biratnagar eye hospital: A tertiary eye care center in Nepal - Agarwal, Lalit; Agrawal, Nisha; Karki, Pratap; Anand, Abhishek (Asian Journal of Medical Sciences, 2016)
Background: A macular hole is a full-thickness defect of retinal tissue involving the anatomic fovea, thereby affecting central visual acuity. Pars plana vitrectomy and gas tamponade is a recognised modality of treatment for macular hole.Larger holes are more likely to remain open after repair and late reopening after an initially closed macular hole is seen in macular holes larger than 400 μm. Aims and Objective: To evaluate the anatomical and functional outcome of pars plana vitrectomy with internal limiting membrane peeling for chronic stage 3 macular hole. Materials and Methods: Records of 15 patients with stage 3 chronic macular holes operated from 1st January 2013 to 30th June 2013 and completed 1 year of follow up were retrospectively evaluated and included in the study. Preoperative best distance corrected visual acuity (BCVA), preoperative macular hole size, final BCVA and macular hole status at 1 year follow up were recorded. Macular hole closure and visual improvement was calculated. Correlation of macular hole closure and visual improvement with various macular hole parameter was estimated. Results: Eleven (73.3%) macular holes closed at 1 year follow-up. Mean BCVA improved from 1.2 ± 0.27 to 0.89 ± 0.36 logarithm of minimum angle of resolution at 1 year (p<0.001). Visual improvement was seen in only eight (53.3%) eyes. Both macular hole closure and visual improvement showed no correlation with minimum linear diameter, base diameter and hole height. Conclusion: Chronic stage 3 macular hole can be closed successfully in majority of patients with fairly good visual improvement. Macular hole parameters of stage 3 holes may not have any correlation with the anatomical and visual outcome. Asian Journal of Medical Sciences Vol.7(6) 2016 43-46